Luteibacter jiangsuensis blood stream infection: a first case report - Takanori Horiguchi; Makoto Sumiyoshi; Eri Nagatomo; Kazuki Sakamoto; Souichiro Ogawa; Naoki Ichinari; Akiteru Yamada; Yuki Rikitake; Chihiro Iwao; Takeshi Kawaguchi; Kunihiko Umekita; Ichiro Takajo; et al. (BMC Infectious Diseases, 2023)
Abstract Background Luteibacter jiangsuensis is a gram-negative aerobic bacillus that was first isolated from soil samples at a pesticide factory in China and reported in 2011. Here, we describe the first case of L. jiangsuensis infection in human. Case presentation A 59-year-old Japanese woman undergoing treatment for Crohn’s disease was admitted to our hospital with fever. Clinical examination indicated catheter-related bloodstream infection. The catheter was removed and meropenem was initiated. Morphologically identical glucose non-fermentative gram-negative bacilli were detected from two sets of aerobic blood culture and catheter-tip cultures. MALDI-TOF mass spectrometry failed to identify the bacterium, which was later identified as L. jiangsuensis by 16 S rRNA gene sequencing. Antimicrobial susceptibility test revealed that the isolate was resistant to carbapenem, therefore meropenem was switched to intravenous levofloxacin (500 mg/day). After 14 days of treatment with levofloxacin, the patient was discharged. Conclusions This is the first case of L. jiangsuensis infection in human. The strain was identified by 16 S rRNA gene sequence analysis.